Competition and Activity Based Costing, play significant Role in Firm Performance - Al-Nuaimi, Safaa Ibrahim Mahmood; Alekam, Jamal Mohammed Esmail; Mohamed, Rapiah (2017)
The present study purpose is to examine the competition and activity based costing, play significant role in firm performance in the banks industry in Iraq.Due to the critical role of banks in Iraqi economic.Activity based costing ABC is a strategic tool that ensures accurate service costs as compared to traditional costing system.The implementation of Activity based costing provides helpful information for performance measurement, planning, cost control and strategic decision-making. Meanwhile in, certain factors such as the Competition between banks determine the motivation of activity based costing implementation and its effect on organizational performance.However, past studies in this field have neither been so emphatic in explaining the important of Competition factor in implementing activity based costing in organizations nor examined the perception of employees and organizations’ decision makers towards the implementing of activity based costing.In addition, the government of Iraq and the Central Bank of Iraq has also issued recommendations to Iraqi banks to consider initiating activity based costing, because of its influence of reduction cost.Therefore, this study is motivated to examine the direct relationships between competition, ABC implementation and firm performance of banks in Iraq.This study surveyed 273 chief accountants of banks in Iraq Out of 402 distributed. The data collected was analyzed using PLD version 2. The study revealed that there is a significant relationship between Competitions; activity based costing Implementation and firm performance. Future researchers are recommended to consider other contingency factors and examine their effect on ABC implementation and firm performance.